2017
DOI: 10.1038/ijo.2017.152
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of body mass reduction-associated activation of brown/beige adipose tissue in patients with type 2 diabetes mellitus

Abstract: Body mass reduction has a more efficient effect to induce the activation of B/BAT in non-diabetic than in diabetic subjects. This effect is accompanied by more pronounced insulin sensitivity and serine 473 phosphorylation of Akt in B/BAT of non-diabetic than in diabetic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
0
12
1
2
Order By: Relevance
“…Interestingly, in the same study, there was no association between 12.5% weight loss and cold‐induced BAT GU even though subjects with obesity had high BAT GU values . In contrast to another study in subjects with morbid obesity, after 8 months of surgery, body mass reduction of around 28% had a more efficient effect to induce BAT activation in non‐diabetic than in subjects with diabetes . Surprisingly, in the present study, there was a significant reduction in BAT mass without any changes in body weight or cold‐induced BAT GU rate.…”
Section: Discussioncontrasting
confidence: 78%
“…Interestingly, in the same study, there was no association between 12.5% weight loss and cold‐induced BAT GU even though subjects with obesity had high BAT GU values . In contrast to another study in subjects with morbid obesity, after 8 months of surgery, body mass reduction of around 28% had a more efficient effect to induce BAT activation in non‐diabetic than in subjects with diabetes . Surprisingly, in the present study, there was a significant reduction in BAT mass without any changes in body weight or cold‐induced BAT GU rate.…”
Section: Discussioncontrasting
confidence: 78%
“…Employing [18F]-fluorodeoxyglucose (FDG) uptake as determined by positron emission tomography combined with X-ray computed tomography (FDG-PET/CT), studies have identified a number of factors that are physiologically related to increased BAT activity, such as cold-exposure, leanness, youth, physical activity and the female gender [13,67,72]. Conversely, in pathological conditions such as obesity and T2D not only is baseline BAT glucose uptake low, but the capacity of inducing its activity by different approaches is impaired [48,54].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, BS displayed a beneficial impact on the metabolic activity of BAT in morbidly obese patients 2 . The increase in brown/beige adipose tissue activity related to surgery-induced weight loss occurs independently of changes in hypothalamic activity 20 and BAT activity was found to be increased in obese nondiabetic and unchanged in obese diabetic subjects submitted to bariatric operation 21 . increased BAT thermogenesis, mediated by higher levels of growth hormone and insulin growth factor 1 6 .…”
Section: Discussionmentioning
confidence: 88%
“…. However, there are few studies showing the effects of BS on BAT and these reports present contrasting data regarding the surgery’s benefits 2 , 10 , 20 , 21 , 27 . Obese subjects showed increased non-shivering thermogenesis in BAT one year after surgery-induced weight loss, demonstrating that BAT can be recruited after bariatric procedures in humans 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation